An Introspection of High School Science Education from South Africa - Chowdhury, Pinaki (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2023)
This century, the twenty-first century, is a century of science and technology explosion. This is the period when the boon of science has arrived in almost every corner of the world. One such example is exposure to information (data) using a cell phone, bypassing a computer. This has made information available to the masses at a much cheaper rate and with less difficulty. This has become possible only because of the science, technology, engineering, and mathematics (STEM)-trained workforces developed by STEM education over the years. One more important aspect of the twenty-first century is the demand for more and more STEM workforces at all levels. As a result, every country is planning hard to achieve their goal of getting more and more STEM-trained workforces for the sustenance of social and economic growth using both the immigration channel and high school STEM education development programs. In order to keep pace, the South African education system is also undergoing changes. Significant adjustments are made in the high school education system to reflect the post-apartheid era's worldview and correct pre-apartheid era-induced mistakes. The 1996 South African Schools’ Act is the beginning of changes in the South African school education system. The purpose of this study is to ascertain whether there has been any improvement in STEM education in general and physical science in particular after all these changes were implemented in the South African school system. The purpose of this study is to establish the empirical hallmark of changes in high school physical science teaching outcomes using a sample from rural South African schools for a period of 2008 to 2018. This study collected secondary data from the national senior certificate examination (NSCE) data base to analyse the teaching-learning outcomes of physical science within a rural school district in the Mpumalanga Province of South Africa. A quantitative analytic method was used to analyse the set of secondary data thus collected. The study concludes that, during the observed period, there has been statistically insignificant improvement in learners' performance in physical science, and there exists a room for introspection regarding the state of high school science teaching processes in order to improve the quality of STEM education in the country.